HELLP SYNDROME. FIVE YEARS OF EXPERIENCE IN THE HOSPITAL "VICTOR LAZARTE ECHEGARAY" - Olivencia, Claudia (2015)
OBJETIVE: To determine the frequency, laboratory results and maternal and perinatal morbidity and mortality in patients with HELLP syndrome. DESIGN: Retrospective descriptive. MATERIALS AND METHODS: Sixteen cases of HELLP syndrome treated at the Victor Lazarte Echegaray Hospital between March 1997 and March 2002. RESULTS: The frequency of HELLP syndrome was 4.9% in pregnant women with a hypertensive disorder, 56.2% with criteria 43.8% complete and partial HELLP. Of the 16 cases, 68.8% had between 25 and 34 years, 43.8% were nulliparous and 37.5% were between 35 and 39 weeks. HELLP occurred in 87.5% in the antepartum. The major obstetric complications were DIC and abruption. Maternal mortality was 3 perinatal cases and 10 cases. CONCLUSIONS: HELLP syndrome is an entity of high maternal morbidity and mortality. The medical and surgical management and intensive care support should reduce the complications associated with this entity.